3GPP long term evolution and its application for healthcare services - Aini Syuhada, Md Zain; Abid, Yahya, Dr.; Mohd. Fareq, Abd. Malek, Dr.; Normaliza, Omar (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/